Palynostratigraphy of the Zorritas Formation, Antofagasta Region, Chile: Insights on the Devonian/Carboniferous boundary in western Gondwana - Rubinstein, Claudia Viviana (2017)
The Middle Member of the Zorritas Formation in the Antofagasta region of northern Chile, yielded terrestrial and marine palynomorph assemblages which span the Devonian/Carboniferous boundary. The assemblages show a clear predominance of terrestrial palynomorphs with 70 miospore species, 18 marine phytoplankton species, two non-marine algae and one chitinozoan species, all coming from 15 productive levels. Palynomorphs are poorly preserved and most of them are reworked. Three palynological associations are recognized based on miospores. These are assigned to the Tournaisian–Visean, Tournaisian and probable latest Famennian. Age assignments are discussed in the frame of the spore zonal schemes established for Euramerica and western Gondwana. The stratigraphical distribution of spores allows the identification of the probable position of the Devonian/Carboniferous boundary within the Zorritas Formation. This system boundary is proposed for the first time in Palaeozoic sedimentary rocks of northern Chile. The presence of Gondwanan typical miospore species indicates affinities with this palaeocontinent even though the Tournaisian and Tournaisian–Visean miospore associations support the cosmopolitanism already suggested for the early Carboniferous flora. The significant number of reworked palynomorphs together with the sedimentological analysis of the studied sections, suggest that these deposits were severely impacted by the climatic change and major sea level fluctuations. Similar conditions were recorded in coeval western Gondwana basins.